2019
DOI: 10.1002/1873-3468.13361
|View full text |Cite
|
Sign up to set email alerts
|

A novel inhibitor of tumorspheres reveals the activation of the serine biosynthetic pathway upon mitochondrial inhibition

Abstract: Differences in the metabolism of cancer cells or cancer stem cells (CSCs) as compared to normal cells have provided avenues to safely target cancers. To discover metabolic inhibitors of CSCs, we performed alkaline phosphatase‐ and tumoursphere‐based drug screening using induced cancer stem cell‐like cells. From the screening of a RIKEN NPDepo chemical library, we discovered NPD2381 as a novel and selective cancer‐stemness inhibitor that targets mitochondrial metabolism. Using our ChemProteoBase profiling, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…It has been established that mitochondrial dysfunction causes changes in one-carbon metabolism and that cancer cells will depend even more on their serine/glycine synthesis upon mitochondrial inhibition (33,34). Furthermore, serine/glycine synthesis and the tricarboxylic acid (TCA) cycle are strongly interconnected, implying that targeting both pathways might further metabolically disrupt cancer cells.…”
Section: Sertraline Has Clinical Potential Especially When Used In Combination Therapymentioning
confidence: 99%
“…It has been established that mitochondrial dysfunction causes changes in one-carbon metabolism and that cancer cells will depend even more on their serine/glycine synthesis upon mitochondrial inhibition (33,34). Furthermore, serine/glycine synthesis and the tricarboxylic acid (TCA) cycle are strongly interconnected, implying that targeting both pathways might further metabolically disrupt cancer cells.…”
Section: Sertraline Has Clinical Potential Especially When Used In Combination Therapymentioning
confidence: 99%
“…Serine transmethylation product (catalyzed by serine hydroxymethyltransferase; SHMT, EC 2.1.2.1), glycine, was decreased in crGART, crPFAS, and crADSL cells. Subedi et al reported higher basal levels of SSP enzymes in HeLa cells [ 51 ]. A study of the NCI60 panel showed that glycine conversion increases the rate of proliferation and significantly supplies PDNS [ 42 ], which were both metabolic processes greatly affected in our study given the cellular model and experimental conditions.…”
Section: Discussionmentioning
confidence: 99%